The Influence of Brand Image, Price and Product Quality on Purchase Decision - Michael Michael; Rahmat Alamsyah Harahap; Albert Albert; Albert Hartanto (Institute of Computer Science (IOCS), 2021)
PT. Cahaya Bintang Medan is a distributor of Richiwa brand furniture. The problems of the purchasing decisions were that the products price were more expensive than similar products from well-known brands, lack of marketing knowledge about the product advantages offered, and the consumers doubted the product quality. The research method used was the quantitative descriptive, the nature of research was the explanatory research. The research population is 192 respondents, by using the Slovin formula, the research sample obtained of 130 respondents, while 30 respondents for testing the validity and reliability with simple random sampling. The analysis method was multiple linear regression with classical assumption testing. The conclusion obtained from this research showed that the effect of brand image, price and product quality simultaneously has a positive effect on purchasing decisions. Partially the brand image of tcount 0.587<ttable 1,65694 and Sig. 0.558>0.05, the price of tcount 1.185<ttable 1.65694 and Sig. 0.238>0.05, the product quality of tcount 2.591>ttable 1.65694 and Sig. 0.011<0.05. The results of determination coefficient test Adjusted R Square of 45%, it means that the purchasing decisions can be explained by the brand image, price and product quality, while the remaining 55% are other factors not examined by researchers.